Water level indicator with electrical valve / Muhd Muqhzeen Zolkaplie, Muhammad Faiz Arsyad Hazizi and Muhammad Taufiq Mohd Ali - Zolkaplie, Muhd Muqhzeen; Hazizi, Muhammad Faiz Arsyad; Mohd Ali, Muhammad Taufiq (2015)
The water level indicator with electrical valve is designed to help people nowadays whom always have problems with their water tank . So, this project may help them to overcome this problem. Other than that, it will help to prevent people to climb up to the roof to check the condition of their tank. So with the existing of this project, it will overcome the problem that will be faced by the people who face the same problem. Our project is based on the demand of the people who has problem with their tank. Especially when they are old and weak .. This project is easy to use and user friendly. It is because people only need to plugged in the plug and just place the rod inside tank . As long as there is power source , this project can work and be observed